Multistage treatment for olive mill wastewater: Assessing legal compliance and operational costs - Vuppala, Srikanth (2022)
A treatment train for the remediation of a raw olive mill wastewater (OMW) was investigated, aiming to comply with the emission limit values (ELVs) for direct discharge into water bodies. The following stages were proposed: (i) pre-treatment (filtration and sedimentation), (ii) coagulation, (iii) biological oxidation, and (iv) advanced oxidation process (AOP). Under the best-operating conditions for coagulation (0.8 g L- 1 of Al2(SO4)3, pH = 4.5), high removal of total suspended solids (TSS) (97%), turbidity (98%), and phenols (57%) was achieved, along with a decrease in the inhibition of the biological activity. A subsequent biological oxidation stage provided a high removal of organic matter (chemical oxygen demand (COD) removal of 73%). For the third stage, three AOPs were applied and compared – photo-Fenton with UVA radiation (PF-UVA), anodic oxidation (AO), and ozonation (O3). After 3 h of treatment, the PF-UVA process (pH = 2.8, [H2O2] = 400–500 mg L- 1, [Total dissolved iron]0 = 100 mg L- 1) allowed to meet the ELV for COD, but the other parameters exceeded the threshold, while O3 process (inlet concentration = 100 mg O3 Ndm- 3, gas flow = 0.2 Ndm3 min- 1) allowed to comply with phenols, TSS, and sulfate limits. The AO process (current density up to 200 mA cm- 2) was the least efficient AOP for all studied parameters. The operational costs for the coagulation and biological oxidation stages were estimated at 1.20 € m- 3. Regarding the most effective AOPs, ozonation presented an estimated cost 2.3-fold higher than PF-UVA (11.9 € m- 3 vs. 5.2 € m- 3).